Effectiveness of Application of TiO2 Nanoparticles in Removing of Heavy Metal Contaminants from Basrah River Water - Anwar A. Jumaa ‎; , Salwa A. Abduljaleel ‎; Abdulzahra A.N. AlHello; A. Abdulnabi, Zuhair (University of Thi-Qar Journal of Science, 2024)
In this study, we focused on the application of Titanium dioxide nanoparticles semiconductor oxides for the removal of heavy metals from Basrah wastewater. Commercial TiO2 was downscaled by ball milling , characterized and tested for heavy metals (Pb, Cd, Hg and Co) removals from the secondary channel of Basrah wastewater (SCBW). Morphology characterization using FT-SEM images indicated that TiO2 particles are of mean grain size 98 nm, Zeta potential measurements revealed the negative charge of the TiO2 particles, X-ray diffraction analysis confirmed anatase phase TiO2 particles , BET measurements exhibited the TiO2 is mesopores with a surface area of 12.65 m2/g , EDX spectrum indicated pure TiO2. The effect of contact time, Temperature, and PH have been taken into account as a parameter to understand the adsorption Mechanism. The best recorded removal percentage was about ( 97 %) for Pb element after 120 minutes with temperature( T=40o ) in Al-Rebat station and reached ( 100 %) for PH=9. This study has shed light on the importance of TiO2 nanoparticles in removing heavy metals from Basrah river water, which resulted in significant decreases in the concentration of several heavy metals and other pollutants.